2016
DOI: 10.1128/aac.01319-16
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of mcr-1 and bla NDM-1 in Escherichia coli from Venezuela

Abstract: bWe studied the presence of the mobile colistin resistance gene mcr-1 in human, animal, and environmental Enterobacteriaceae samples from Cumana, Venezuela, that were collected in 2015. The mcr-1 gene was detected in 2/93 Escherichia coli isolates from swine (novel ST452) and human (ST19) samples that were resistant to colistin. Whole-genome sequencing and transformation experiments identified mcr-1 on an IncI2 plasmid. One of the isolates also bore the widely spread carbapenemase NDM-1. A One Health approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 12 publications
(10 reference statements)
2
67
0
2
Order By: Relevance
“…In agreement with proposal by Petrillo and coauthors [43], the deletion of this IS Apl1 insertion sequence might be the relic of the mcr-1 dissemination. It was reported that the mcr - 1 colistin resistance gene is present in a multidrug-resistant plasmid [22] or coexists with other resistance genes like extended spectrum β-lactamase [16,1921], and even the notorious NDM-1 [44] and its variants (NDM-5 [23] and NDM-9 [24]). We also found that the pE15017 is an ESBL and MCR-1 coproducing plasmid similar to pA31-12, a recently-isolated plasmid from China [30].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with proposal by Petrillo and coauthors [43], the deletion of this IS Apl1 insertion sequence might be the relic of the mcr-1 dissemination. It was reported that the mcr - 1 colistin resistance gene is present in a multidrug-resistant plasmid [22] or coexists with other resistance genes like extended spectrum β-lactamase [16,1921], and even the notorious NDM-1 [44] and its variants (NDM-5 [23] and NDM-9 [24]). We also found that the pE15017 is an ESBL and MCR-1 coproducing plasmid similar to pA31-12, a recently-isolated plasmid from China [30].…”
Section: Discussionmentioning
confidence: 99%
“…With the high levels of antibiotic prescription in medicine and unregulated antibiotic use in agriculture around the world it is likely that it is only a matter of time before completely pan-resistant plasmids are found that combine the above resistance mechanisms. Indeed, the coexistence of NDM1 and MCR1 in members of the Enterobacteriaceae has already been observed 55,132 , and a recent report documented the co-transfer of mcr1 and ndm5 on a mobile hybrid IncX3–X4 plasmid 133 .…”
Section: Figurementioning
confidence: 93%
“…Based on Delgado-Blas et al [194], Di Pilato et al [195], Jeannot et al [168], Kong et al [196], Liu et al [192] and Mediavilla et al [197]. A, animal origin; E, environmental origin; F, food origin; H, human origin; W, wildlife origin.…”
Section: Figurementioning
confidence: 99%